IMPACT OF INFORMATION TECHNOLOGY ON ACHIEVING DIGITAL CONTENT DISTRIBUTION - Dr. Rabie Yassin Saud; Marwa Moayed Fadel (Scholar Express Journals, 2022)
This research aims at identifying the role of information technology in achieving digital content distribution. The problem of research identifies several questions about the extent to which the variable of information technology can be adopted to promote the digital content distribution. To address the problem of research, a set of hypotheses that are appropriate to the problem of research and its objectives have been formulated. A hypothesis was designed showing the correlation and effect relationship between the variables, and some of the Iraqi private colleges were selected as a research population, including (AlNusour University College, Al-Mashreq University, Baghdad College of Economic Sciences, Al-Mamoun University College( to apply the scientific aspect of research and rely on a random sample of its (80) staff respondents. The questionnaire was used as a key data collection tool and analysed by readymade software package (SmartPLS). In the light of the findings, the research found a set of conclusions, the most important of which was that the results of the statistical analysis revealed the direct impact of information technology on the digital content distribution, demonstrating the need for attention to information technology. In the light of the findings of the research, a set of recommendations were suggested, most importantly, greater attention should be paid to the digital content distribution variable as one of the intellectual trends in the contemporary literature in e-marketing, and its impact in achieving successful content marketing, and achieving the competitive advantage for business organizations shoud be highlighted
Keywords: Information technology; Digital content distribution; suggested